Bridging the Gap between Social Sciences and Defense Studies: How the Constructivist Approach Can Enhance Practical Analysis of the Ukrainian War (Journal of Advanced Research in Social Sciences, 2025)
This paper argues that, despite a robust interdisciplinary connection between social sciences and defense studies, a significant omission exists: the absence of social sciences in analyzing actual military operations and belligerents’ capabilities during high-intensity warfare. It emphasizes the importance of constructed identities and perceptions given to adversaries and one’s self-representation in relation to them. It combines an exploration of potential reasons for this absence and an exploratory theoretical constructivist framework applied to specific cases from the Russo-Ukrainian conflict. It posits that such an approach can yield more accurate assessments of belligerents’ capabilities, ground realities, and enhance strategic decision-making. The analysis focuses on discourses surrounding “human wave tactics” and “combined arms”, suggesting they may have been distorted by identity perceptions, affecting capability assessments. This distortion may arise from the tendency to demonize adversaries while idealizing one's own capacities. Recommendations include integrating identity analysis tools in operational assessments.